2019
DOI: 10.1002/cctc.201802040
|View full text |Cite
|
Sign up to set email alerts
|

Phase‐Dependent Stability and Substrate‐Induced Deactivation by Strong Metal‐Support Interaction of Ru/TiO2 Catalysts for the Hydrogenation of Levulinic Acid

Abstract: The choice of support type has a profound influence on catalyst performance in liquid phase hydrogenation reactions, including the catalytic hydrogenation of biomass‐derived levulinic acid (LA) to γ‐valerolactone (GVL). Catalytic performance, including stability, of three Ru/TiO2 catalysts, having a similar mean Ru metal nanoparticle size but supported on three types of TiO2, namely P25, rutile and anatase, is evaluated by multiple reuse under batch reactor conditions. T3he catalysts’ physicochemical propertie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
23
0

Year Published

2020
2020
2025
2025

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(25 citation statements)
references
References 67 publications
(183 reference statements)
2
23
0
Order By: Relevance
“…32 The group of Weckhuysen have further reported the absence of any sintering when Ru was supported on a mixed phase as well as on pure rutile supports, while Ru sintering was observed on pure anatase phase. 33 Further, Sassoye et al indicated that the migration of RuO2 can be observed from the anatase to the rutile phase when the TiO2 support contains both polymorphs. 34 This confirmed the existence of weaker interactions of the supported Ru species with the anatase phase than with the rutile phase.…”
Section: Figurementioning
confidence: 99%
See 1 more Smart Citation
“…32 The group of Weckhuysen have further reported the absence of any sintering when Ru was supported on a mixed phase as well as on pure rutile supports, while Ru sintering was observed on pure anatase phase. 33 Further, Sassoye et al indicated that the migration of RuO2 can be observed from the anatase to the rutile phase when the TiO2 support contains both polymorphs. 34 This confirmed the existence of weaker interactions of the supported Ru species with the anatase phase than with the rutile phase.…”
Section: Figurementioning
confidence: 99%
“…34 The group of Weckhuysen also evidenced that the Ru catalyst stability depended on the crystallographic nature of the titania support, strong sintering being observed on pure anatase, while an irreversible reduction of the anatase support caused by strong levulinic acid adsorption induced the SMSI effect. 33…”
Section: Please Do Not Adjust Marginsmentioning
confidence: 99%
“…For example, Zhang et al observed smaller ruthenium nanoparticles on TiO 2 anatase than on TiO 2 rutile, 24 whereas other authors observed smaller ruthenium nanoparticles and a more homogeneous repartition of nanoparticles on TiO 2 rutile. [27][28][29][30] In this paper, the impact of TiO 2 support on the reactivity of ruthenium catalysts in xylose hydrogenation was investigated with a focus on the differences in reactivity observed when different supports are used. Two catalysts with two different commercial TiO 2 , anatase and rutile, were prepared, characterized and tested for xylose hydrogenation.…”
Section: Introductionmentioning
confidence: 99%
“…[6,7] Yet, impermeable and thick support layers over the catalysts can also lead to a decrease in performance by blocking active sites. [8,9] Therefore, probing the existence and specific role of the encapsulation layer of SMSI materials is crucial to understand their performance in catalytic reactions. Although the existence of thin encapsulation layers on metal catalysts was recently proved by electron microscopy, [10][11][12][13][14] structure-property relationships were rarely investigated, especially in the case of electrochemical properties.…”
Section: Introductionmentioning
confidence: 99%